Revision of the Japanese species of Trichoclinocera Collin (Diptera: Empididae: Clinocerinae) - Saigusa, Toyohei; Sinclair, Bradley J. (Zootaxa, 2016)
The Japanese species of Trichoclinocera are revised and include nine species, of which seven are new species (T. dasy-scutellum (Saigusa), T. fuscipennis Saigusa, T. gracilis sp. nov., T. grandis sp. nov., T. miranda sp. nov., T. setigera sp. nov., T. shinogii sp. nov., T. stigmatica sp. nov., T. takagii sp. nov.). A key to all nine species is provided, their distributions mapped and affinities discussed.